The Issue of the Invasive African Giant Snail in the Debate around Public Health, Malacology and Environmental Bioethics: A Sustainable Development Goals Agenda (Revista Iberoamericana de Bioética, 2020)
Environmental Bioethics has a role to play in the resolution of the many complex global challenges involved in achieving the Sustainable Development Goals, such as issues surrounding animals that cause damage to human health, the environment and the economy. Such is the case of the giant African snail, one of the hundred most damaging invasive species in the world. The issue of its control generates differences of opinion between competing social interests and public managers regarding ethics in the treatment animals. Faced with this seemingly insoluble problem, given its breadth, complexity and diversity of possible outcomes, a reflection based on technical and ethical principles is put forward.
Keywords: Achatina fulica; invasive alien species; vulnerable populations; urban pests; public health; global health